The Influence of Understanding Taxes and Tax Sanctions on the Compliance of Individual Taxpayers Who Own MSME Businesses in Pagar Dewa Subdistrict, Bengkulu City - Mia Margareta Huta Galung; Karona Cahya Susena; Yudi Irawan Abi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
There are many small and medium businesses in Pagar Dewa Village, Selebar Bengkulu Sub-District, namely 80 MSME owners. This research aims to determine the effect of tax understanding and sanctions on the compliance of individual taxpayers who own MSME businesses in Pagar Dewa Village, Bengkulu City. This research is explanatory in nature. The sampling technique in this research uses a total sampling technique, where the samples taken are private taxpayers who own MSME businesses in Pagar Dewa Village, Bengkulu City. Data collection techniques in this research are observation, questionnaires and literature study. Based on the results of this research and data analysis, the result F table is 2.95 because F count > F table (7.894 > 2.95) then Ha is accepted and Ho is rejected, meaning that the variables have a significant effect on tax understanding (X1), tax sanctions (X2) and service quality (X3) together or simultaneously towards taxpayer compliance (Y). The termination coefficient value of Adjusted R Square R2= 0.774. This value means that the independent variables together contribute 77.4% in influencing the dependent variable with medium criteria.